Implementation of Zone-Based Student Admission (PPDB) Through Website in Purwakarta: Challenges and Benefits - Supendi, Dede; Komariah, Aan; Munir, Munir; Suryadi, Suryadi (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: This study investigates the implementation of the Zone-Based Student Admission (PPDB) System through a website in Purwakarta, Indonesia, highlighting the challenges and benefits of this educational transformation. Amid demographic changes, economic shifts, and evolving educational priorities, reforming the student admission process has become an urgent necessity. The challenges in its implementation include adaptation to change, capacity building, and technical infrastructure. Conversely, the webbased PPDB system offers multiple advantages. It promotes equity and fairness by providing equal opportunities, especially for marginalized communities, enhances transparency through easily accessible admission rules, real-time updates, and consistent procedures, simplifies student enrollment with automated processes, and reduces administrative costs through streamlined procedures. This study utilizes a literature review approach, drawing from various sources such as reports and articles that focus on the challenges and benefits associated with the PPDB system in Purwakarta and in Indonesia in general. In conclusion, despite the challenges, the implementation of the webbased PPDB system in Purwakarta represents a significant step towards a more equitable and efficient educational system. Carefully navigating the challenges and leveraging the system's advantages promises a more inclusive, transparent, and efficient educational landscape in Purwakarta. Keywords: Zone-Based Admission, Website Implementation, Purwakarta Education.